Electric Field Modulation of Silicon upon Tethering of Highly Charged Nucleic Acids. Capacitive Studies on DNA‐modified Silicon (111). Issue 10 (6th October 2016) - Gebala, Magdalena; La Mantia, Fabio; Michaels, Pauline Eugene; Ciampi, Simone; Gupta, Bakul; Parker, Stephen G.; Tavallaie, Roya; Gooding, J. Justin
Abstract: We provide complex capacitance studies which show that the tethering of negatively‐charged DNA molecules to p‐doped silicon (111), without intervening oxide layer, leads to changes of the electric field in the underlying silicon. We proposed, that the tethering of the DNA leads to the formation of surface states that, from the electronic point of view, resemble the major carriers of p‐type silicon, i.e. holes. This effect is enhanced by the formation of double‐stranded (ds)DNA molecules and hence is the premise to label‐free detection of the DNA hybridization. Overall, our studies provide a promising alternative to design a biosensor to detect the hybridization of DNA molecules on the silicon surface. Abstract :